Ecoprint Motif Analysis Using Young Teak Leaves with Tunggung Fixation Applied to Artificial Fibers - Farihah; Winda Hastuti; Halimul Bahri; Yudhistira Anggraini (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to analyze the effect of tunjung (ferrous sulfate) fixation duration on the color quality and motif clarity of ecoprinted fabrics made from young teak (Tectona grandis) leaves applied to artificial fibers. The research supports the development of eco-friendly natural dye applications and innovation in textile and fashion education. A descriptive quantitative method was used, employing trend and percentage analyses based on evaluations from three textile experts. The assessment covered five aspects: color brightness, motif clarity, motif arrangement neatness, cleanliness, and overall appearance. The results showed that fixation durations of 10, 30, and 60 minutes did not significantly influence color brightness or motif quality, indicating that the dye–fiber bonding equilibrium was achieved within 10 minutes. However, qualitative observations revealed that samples fixed for 30 minutes exhibited slightly clearer motifs due to mild oxidation and pigment redistribution during steaming and drying. These findings suggest that a 10-minute fixation duration is sufficient for efficient dye bonding, while a 30-minute duration may enhance visual definition. The study contributes to sustainable textile innovation by demonstrating that teak leaf pigments combined with tunjung mordant can produce eco-friendly, visually appealing fabrics suitable for fashion and textile learning.